Semantic Web Representation for Phytochemical Ontology Model - Hamiz, M.; Haron, Haryani; Sanusi, Azlin; Bakri, M.; Mohd Nazaruddin, Nur Syamira (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Nowadays people are more health conscious; they monitor the ingredients and nutrients of what they eat. Fruits and vegetables, which are rich of phytochemicals, are always chosen as a good diet. Phytochemicals are rich of nutrients and can give health benefits to the takers. Previous research has modelled the phytochemicals into its chemical structure and colours according to group of fruits and vegetables ontologically. However, there is no semantic web representation of that ontology model that makes the information more sharable among users. Therefore, in this paper, we develop a semantic web for phytochemical ontology model by linking the user interface to ontology model using JENA framework. The data from the ontology is read by using SPARQL query to display information to the front-end user. By having this semantic web representation, it is hoped that the knowledge is more accessible and shareable among intended users.